Aplikasi Steganografi Menggunakan LSB 4 Bit Sisipan dengan Kombinasi Algoritme Substitusi dan Vigenere Berbasis Android - Priyagung Hernawandra; Supriyadi Supriyadi; U. Tresna Lenggana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This study aims to implement steganography with 4 bit LSB method combined with Vigenere and substitution encryption algorithms. This combination strengthens the security of text messages that are inserted into the image because the message is already a ciphertext as the result of the Vigenere and substitution encryption process. This steganography is realized as an application that runs on Android devices. This application can insert text messages that contain space characters and a combination of uppercase letters in a digital image. Using this application, insertion of messages into images causes the increase of images size by an average of 12.77% of the original size from 10 sample images.